Never-ending war on terror - Lubin, Alex (Oakland, California: University of California press, 2021)
"An entire generation of young adults has never known an America without the War on Terror. This book contends with the pervasive effects of post-9/11 policy- and myth-making in the United States in every corner of American life. Never-Ending War on Terror is organized around five keywords that have come to define the cultural and political moment: homeland, security, privacy, torture, and drone. Alex Lubin synthesizes nearly two decades of United States war-making against terrorism by asking how the War on Terror has changed American politics and society, and how the War on Terror draws on historical myths about American national and imperial identity. From the PATRIOT Act to the hit show Homeland, from Edward Snowden to Guantanamo Bay, and from 9/11 memorials to Trumpism, this succinct book connects America's political economy and international relations to our contemporary culture at every turn"--
An introduction without a beginning -- Mourning in America -- Privacy and security -- Liberal torture -- Extrajudicial assassination by drone -- A conclusion without an ending.
Includes bibliographical references.
Keywords: War on Terrorism, 2001-2009 -- Social aspects -- United States; War and society -- United States -- History -- 21st century